Analisis Pengaruh Kemiskinan, Pengeluaran Pemerintah Dan Pertumbuhan Ekonomi Terhadap IPM Di Kabupaten Sumbawa - Risma Nur Aulia Pratiwi Herman; Sri Muljaningsih (Universitas Hamzanwadi, 2022)
HDI is an important indicator of development. There are three dimensions to realizing the HDI, namely a long and healthy life, knowledge and an adequate standard of living. This study aims to determine and analyze the effect of poverty, government spending on education, government spending on health, and economic growth on the human development index (IPM) in Sumbawa Regency. This research uses an explanatory with a quantitative approach. The data of this research, namely secondary data, includes the value (number) of poverty data, government spending on education, health, economic growth and the human development index (IPM) in Sumbawa Regency for the 2010-2020 period which was obtained from the official website of the Badan Pusat Statistik (BPS) and the Regional Financial and Badan Pengelolaan Keuangan dan Aset Daerah (BKAD) of Sumbawa Regency. The results of this study indicate that partially, the results of the significance of poverty (X1) of 0.084 meaning that it is not significant to the HDI, government spending on education (X2) of 0.721 meaning that it is not significant to HDI, government spending on health (X3) of 0.038 which means that it has a significant effect on the HDI. HDI, and economic growth (X4) of 0.677 means that it is not significant to the HDI. And simultaneously, that there is an effect between X1, X2, X3 and X4 on Y (IPM) with the results of F-count F-table or 33,204 4.12 and a significance value of 0.000 0.05.